Perbadingan Kemampuan Berpikir Kritis Siswa antara Problem Based Learning dengan Inquiry Learning - Ellen Proborini; Fajar Husain Asy’ari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2025)
The research aims to determine the differences in applying the PBL and Inquiry learning models to students' critical thinking skills. The subjects of this study were class XI TBKR and XI TAB SMK Tunas Harapan Pati in the 2023/2024 academic year. The data used in this study were obtained from pretests and posttests. The pre-test is to determine that the sample has the same ability, while the poster determines the difference in ability after being given the given model. The post-test scores are explained using the dependent t-test (paired t-test). Before being analyzed with the dependent t-test, the second score was first tested for normality using the Lilliefors formula and the homogeneity test using the Barlett test. The average posttest results for students who were given PBL was 87.08, while for students who were given inquiry was 79.48. Based on the hypothesis test, the conclusion is that applying the PBL learning model gives students better critical thinking skills than students who are given the inquiry learning model.